The Relationship Between Children's Birth Time and Short Stature - Wang, Shuo; Shao, Na; Ding, Yiyi; Cai, Hong; Zou, Runmei; Wang, Cheng (Frontiers in Pediatrics, 2022)
Background There are few current reports on the relationship between time of birth and short stature in children. Therefore, we aimed to investigate whether there is an association between time of birth and short stature in children. Materials and Methods In this study, basic information was collected from 462 children aged 2–14 years old. We collected data on gender, height, height standard deviation score (SDS), weight, body mass index (BMI), serum 25(OH)D levels, date of birth, and whether the above children were short stature. Demographic description, univariate analysis, multivariate logistic regression analysis, smooth curve fitting, and threshold effects were used to explore possible linear or non-linear relationships between children's birth time and short stature. Results The mean age of the 462 children was 9.76 ± 3.10 years old, and 52.16% were male. A total of 129 (27.92%) children were defined as 25(OH)D insufficiency, including 107 (38.91%) in the short stature group and 22 (11.76%) in the normal stature group. Fully adjusted logistic regression showed that the risk of short stature was reduced by 56.5% in children born in summer compared with spring (P < 0.05) [odds ratio (OR): 0.435, 95% confidence interval (CI): 0.197–0.959]. A non-linear relationship was found between “sequential day of the year” and short stature from the 1st to the 250th day of the year, the risk of short stature in children is reduced by 0.6% for each day that passes (P = 0.002) (OR: 0.994, 95% CI: 0.990–0.998), and from the 250th to the 365th day of the year, the risk of short stature in children was increased by 0.8% for each day that passed (P = 0.008) (OR: 1.008, 95% CI: 1.001–1.025). Conclusions Children born in summer have a lower risk of short stature than spring. For children born before the 250th day of the year, “sequential day of the year” was negatively associated with short stature, and for children born after the 250th day, “sequential day of the year” was positively associated with short stature.